Gender differences in entrepreneurial intention among university students / Siti Meriam Ali... [et al.] - Ali, Siti Meriam; Law, Kuan Kheng; Mahshar, Mursyida; Mohd Ngisomuddin Masduki, Raden (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2018)
The purpose of this study is to examine gender differences in attitude, perceived behavioral control, subjective norm and entrepreneurial intention among university students. A self-administered and structured questionnaire was employed in eliciting responses from one hundred and forty-three (143) undergraduates of University Teknologi MARA in Kedah. An independent sample t-test was conducted to compare the study variables scores for male and female students. The test of equality of variance shows that the p-value is higher than 0.05 for majority of the studied variables, hence this indicates that there is no significant difference between the two groups. However, results have revealed that there is a significant difference in the entrepreneurial intention between male and female students. Male students (M=3.8882) has significantly higher entrepreneurial intention than female students (M=3.570). The finding of this study provides useful implication for academic institutions and policy makers in enhancing entrepreneurial participation among university students. An effective entrepreneurial programs and activities can be designed based on the gender specific needs.